Islamic Da'wah in Environmental Issues: Tiktok Metro Tv's Content Analysis on Bali Floods - Ulfa, Marya; Sari, Nur Rovida Femila; Hamidah, Lilik (UIN Fatmawati Sukarno Bengkulu, 2025)
This study examines the role of Islamic da'wah in environmental issues by highlighting the major flood that occurred in Bali on September 10, 2025. The low level of public awareness and concern for environmental preservation, which caused the flood, was not only due to natural factors but also due to environmental damage caused by human activities, as well as the suboptimal role of Islamic da'wah in building ecological awareness in society. This study uses a descriptive qualitative method with content analysis. The purpose of this study is to analyze the role of da'wah (Islamic outreach) on environmental issues, specifically through TikTok Metro TV's social media content, in educating the public about the causes and impacts of flooding. This data was obtained from TikTok Metro TV's social media platforms in the form of videos, observations of information broadcasts, and literature on Islamic da'wah and ecology. This study shows that flooding in Bali is not only caused by extreme rainfall, but also by decreased land absorption capacity, development that ignores spatial planning, dense buildings, and community habits that are less concerned about environmental issues, such as littering. Metro TV, through its TikTok account, plays a role in educating the public through short content explaining the causes and impacts of the floods in Bali. From an Islamic ecological perspective, environmental damage is seen as a facade of the earth's purpose (fil-ardh) and must be prevented. Therefore, collaboration between the community, government, media, and Islamic values is crucial to promote disaster mitigation and maintain environmental sustainability.